Routing protocols based on node selection for freely floating underwater wireless sensor networks: a survey - Ghida Jubran Alqahtani; Fatma Bouabdallah (EURASIP Journal on Wireless Communications and Networking, 2023)
Abstract Recently, there has been an increasing interest in monitoring and exploring the underwater environment for scientific applications such as oceanographic data collection, marine surveillance, and pollution detection. Underwater acoustic sensor networks (UASN) have been proposed as the enabling technology to observe, map and explore the ocean. Due to the unique characteristics of underwater aquatic environment, which are low bandwidth, long propagation delays, and high energy consumption, the data forwarding process is very difficult. This paper presents a survey of the routing protocols for UASN. The addressed routing protocols are classified from a mobility point of view in freely floating underwater sensor networks. Indeed, managing the mobility of freely floating underwater sensors is one of the most critical constraints in the design of routing protocols. That is why we classify the routing protocols into “reliable data forwarding protocols” and “prediction-based data forwarding protocols.” In the first category, the proposed protocols mainly endure nodes’ mobility by continuously updating location information aiming at delivering the packets to the sink. In the second category, routing protocols try to rather master the nodes’ mobility by predicting the future nodes’ positions either based on a mobility model or on historical nodes’ positions using filtering techniques. We believe that our classification will help not only in deeply understanding the main characteristics of each protocol but also in investigating the evolution of research work evolution to provide energy-efficient data forwarding solutions for freely floating UASN.